Non-normal Data Simulation using Piecewise Linear Transforms. Issue 1 (2nd January 2022) - Foldnes, Njål; Grønneberg, Steffen
ABSTRACT: We present PLSIM, a new method for generating nonnormal data with a pre-specified covariance matrix that is based on coordinate-wise piecewise linear transformations of standard normal variables. In our presentation, the piecewise linear transforms are chosen to match pre-specified skewness and kurtosis values for each marginal distribution. We demonstrate the flexibility of the new method, and an implementation using R software is provided.